Development of automatic number plate recognition software and journey time measurement /Amri Mohd Yasin - Amri, Mohd Yasin (2012)
There are many useful applications for automatic number plate recognition (ANPR) system such as traffic law enforcement, car toll collection, parking system management and journey time measurement. Among many other advanced techniques to measure journey time, ANPR system has gained lots of intentions because it is a non-intrusive approach and this system does not require any additional vehicle identification to be installed in the vehicle. The aim of this research is to develop offline ANPR software, which can locate and read the number plate with an average rates of more than 80% and to extend the measurement capability of the developed ANPR software for measuring the vehicles journey time. The proposed ANPR software has been developed to suit with the traffic environment in Malaysia. The development of the ANPR software consists of several processing steps: vehicle detection, number plate localization, number plate extraction, character segmentation and character recognition. Several tests were done in order to measure the performance and capability of the developed ANPR software. Based on the results, the system is reliable and robust and its capability to measure journey time indicated that it has a huge potential to be used in traffic and transportation studies.